Does willingness to pay increase with the number and strictness of sustainability labels? - Eva Tebbe; Korbinian von Blanckenburg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Labels signaling sustainable product attributes are gaining importance, although uncertainty concerning the environmental, micro- and macroeconomic benefits of such labels persist. One of the questions still incom-pletely answered is whether Willingness To Pay (WTP) varies with a gradually increasing number of labels on a food product. In order to answer this question, we conducted a laboratory experiment with 191 student respondents, testing consumer valuations of different labeling strategies. Using the Becker-DeGroot-Mar-schak mechanism, WTP for 15 food products was measured. The products were endowed with up to six different sustainability labels, such that each grocery item was available in eight product versions. For perishable, non-perishable and plant-based products, the results indicate that participants are prone to allo-cating WTP-premiums to labeled products, more than to unlabeled products. For animal products, however, labels do not influence WTP significantly. Furthermore, the premiums do not vary with an increasing num-ber of labels, irrespective of whether the labels signal substitute or complementary sustainability infor-mation. The results are not entirely in line with normative notions of magnitude variation, but rather with the behavioral economic concept of embedding effects.
Keywords: D11; D12; D44; L15; 330; Behavioral economics; Experimental economics; Willingness to pay; Becker-DeGroot-Marschak mechanism; Organic; Embedding effect